Brumadinho: capital social e transtornos mentais de um desastre sociotécnico - Rejane Maria Soares (2023)
This study focuses on analyzing the impacts of the sociotechnical disaster in Brumadinho, which occurred on January 25, 2019. It was when the B1 tailings dam of the Córrego do Feijão mine, operated by Vale S.A., ruptured, resulting in the entrapment of victims under toxic tailings mud. The aim is to elucidate the connections between social capital, social support, and the mental disorders that affected and continue to affect the close relatives of the disaster victims. This research served as the foundation for the completion of this thesis. The in-depth analysis of these connections was guided by the hypothesis that the reduction of social capital levels in the personal networks of close relatives of disaster victims is inversely associated with the severity of mental disorders that emerged in the post-disaster period. This formed the basis for examining the internal consistency of this hypothesis and exploring the connections between social capital, social support, and mental health in the socio-spatial context of Brumadinho. This was achieved through triangulation of the theoretical and methodological framework of social network analysis, psychoanalysis, and the structured interview MINI. Contrary to excessively individualistic or biomedical views, this thesis primarily aimed to reveal the centrality of personal networks and psychological support in mitigating the damages and suffering experienced by those directly affected by socioenvironmental disasters.